1996
DOI: 10.1088/0953-8984/8/43/026
|View full text |Cite
|
Sign up to set email alerts
|

Temperature- and pressure-induced structural transitions in rare-earth-deficient (R = Y, Sm, Gd, Tb) Laves phases

Abstract: Electrical resistivity, thermal expansion, and temperature-dependent x-ray diffraction measurements on compounds give mutually consistent evidence for structural phase transitions at 740 K, 550 K, 600 K, and 450 K respectively for R = Y, Sm, Gd, Tb; 0 < x < 0.05. Arguments are given as to why most of the rare-earth - nickel compounds with the 1:2 ratio do not crystallize in the simple cubic Laves phase (C15 type) but show a superstructure of the cubic Laves phase at room temperature and at ambient pressure. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 12 publications
(17 reference statements)
1
38
0
Order By: Relevance
“…This superstructure is formed by a periodic arrangement of vacancies on the RE sites within the normal Laves phase structure giving a doubled lattice parameter and the new space group F 43m due to the reduced symmetry [122][123][124]. At a critical temperature, a reversible transformation from the superstructure to the C15 structure takes place [125]. The simple C15 structure could also be obtained at room temperature by applying pressures of 8 to 27 GPa [125][126][127].…”
Section: Pressure-dependent Transformations In Systems With Two Lavesmentioning
confidence: 99%
See 1 more Smart Citation
“…This superstructure is formed by a periodic arrangement of vacancies on the RE sites within the normal Laves phase structure giving a doubled lattice parameter and the new space group F 43m due to the reduced symmetry [122][123][124]. At a critical temperature, a reversible transformation from the superstructure to the C15 structure takes place [125]. The simple C15 structure could also be obtained at room temperature by applying pressures of 8 to 27 GPa [125][126][127].…”
Section: Pressure-dependent Transformations In Systems With Two Lavesmentioning
confidence: 99%
“…At a critical temperature, a reversible transformation from the superstructure to the C15 structure takes place [125]. The simple C15 structure could also be obtained at room temperature by applying pressures of 8 to 27 GPa [125][126][127].…”
Section: Pressure-dependent Transformations In Systems With Two Lavesmentioning
confidence: 99%
“…The concentration of R vacancies decreases from a few percent for R = Pr to zero for R = Lu [1,2] We have recently shown by a 111 Cd perturbed angular correlation (PAC) study [3] that these vacancies are highly mobile at room temperature and that for R = Pr, Nd, Sm and Gd they can be trapped by the PAC probe 111 Cd. Although 111 Cd resides on the cubic R site of the C15 structure, in some of the paramagnetic RNi 2 111 Cd is therefore subject to an axially symmetric quadrupole interaction (QI) produced by the trapped vacancies.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the RNi 2 samples prepared in the course of this study, measurements were also carried with the single-phase compounds Sm 0.95 Ni 2 , GdNi 2 , Tb 0.98 Ni 2 , and Y 0.95 Ni 2 , which have been previously studied and characterized by resistivity, thermal expansion, and x-ray diffraction measurements. 7 The influence of the indium concentration on the fraction of probe nuclei subject to an axially symmetric QI was investigated by adding stable indium with concentrations of 1 and 3 at.% to samples of SmNi 2 and PrNi 2 .…”
Section: A Sample Preparation and Equipmentmentioning
confidence: 99%
“…According to recent experimental data [5][6][7][8][9] and theoretical studies, 10 RNi 2 does not crystallize in the pure cubic C15 structure, observed, e.g., in RCo 2 . Single phase compounds can only be obtained for rare-earth-deficient R 1−x Ni 2 .…”
mentioning
confidence: 93%